PENGABDIAN KEPADA MASYARAKAT USAHA PANGAN LOKAL BERBASIS TEPUNG UBI DI TEMPILANG KABUPATEN BANGKA BARAT - Zaldy Kurniawan; Muhammad Subhan (Jurnal Pengabdian Masyarakat Polmanbabel, 2021)
The development of various processed cassava with good quality will support local government programs in realizing food security through the development food diversification of local, namely cassava. This Community Partnership Program (PKM) activity is the Ubi Flour Processing Business Group in Tempilang Village. The sweet potato flour produced is made of processed products such as aruk rice, sweet potato noodles, and cakes. From the survey and analysis together with partners, the problems faced by partners, namely regarding production problems related to increasing production capacity and aspects of business management. So far, the process of the production stage is done manually which requires a lot of manpower and time so that it is less productive. From these conditions, the solution taken is first to procure a cassava flour squeezer which has a function to squeeze the sweet potato flour with the help of a threaded shaft drive system and a hydraulic pump with a tool capable of 5 Kg at a time, second is to carry out training on machine operation and maintenance so partners understand about the use and maintenance of tools properly and correctly, and third is to evaluate and monitor partners to measure the success rate of production problems, whether there has been an increase or not. During monitoring, before the press, the production process takes 30 minutes to produce 5 kg of sweet potato flour. However, with the squeezer it takes only 5 minutes to produce 5 kg of sweet potato flour.